Application of information technology in facilities management system in Malaysian Universities / Riswan Effendi Baharuddin - Baharuddin, Riswan Effendi (2008)
Facilities management is steadily gaining influence as a major player in the building industry. With awareness towards building preservation and lifecycle prolonging increasing with every step of development, facilities management will soon be a household term in Malaysia's construction industry. In this modem age, facilities management is closely linked with building automation, and consequently, the application of information technology in facilities management. But in actuality, computers and software have not been good bedfellows with professions in the building and construction industry. Therefore we should ask ourselves this question: how much do we understand about information technology? Is it only a form of communication? Or is it only a set of screens that tells us when our facilities are in trouble? This study will explore the importance of IT in facilities management, especially in the role of database and information management, upon which facilities managers rely so heavily upon.